Implementasi Purwarupa Sistem Pemantau Suhu Serta Kelembaban Berbasis XBEE Sensor Network dan Arduino Uno - Mario Kitsda M Rumlawang; Wijaya Kurniawan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Temperature and humidity monitoring based on WSN (Wireless Sensor Network). Monitoring system based on WSN has advantages compared to cable-based in addition to installation, maintenance and repair costs. The use of XBEE-S2 is better used for long-term monitoring than nRF because it only uses a 3.3 v low voltage. Even though it is expensive in terms of cost, if it is calculated for the long term it will be better if you have to replace it regularly. The simple implementation of the temperature and humidity monitoring system in the XBEE sensor network based building can be applied in chicken farms which helps to monitor the incubator temperature remotely and the use of Arduino as a Microcontroller is the right choice because of features that match the XBEE character that requires TX and RX pins and DHT-11 sensors that require a lot of pins. The choice of topology in sending data is also very important to know before installing the system to get maximum results. The node sensor uses Arduino uno and uses the XBEE-S2 module as a medium for sending and receiving data and uses two different Topologies, star topology and tree topology, which tests distance and throughput are displayed directly on the XCTU program. Testing with tree topology has the highest throughput of 0.31 Kbps and the lowest is 0.03 Kbps while the star topology reaches the highest number of 0.59 Kbps and the lowest is 0.51 Kbps. This is due to the delivery of the star topology directly to the Coordinator.